Fabrication of nanocrystalline λ-Ti3O5 with tunable terahertz wave transmission properties across a temperature induced phase transition. Issue 43 (21st October 2016) - Shi, Qiwu; Chai, Guoqing; Huang, Wanxia; Shi, Yanli; Huang, Bo; Wei, Dan; Qi, Jianqi; Su, Fuhai; Xu, Wen; Lu, Tiecheng
Abstract : Nanocrystalline λ-Ti3 O5 was fabricated by carbothermal reduction of nano-TiO2 . It exhibits a continuous and slow phase transition across a wide range of temperatures, which can lead to dynamic tuning of THz transmission. Abstract : λ-Ti3 O5 was a newly discovered material with intriguing phase transition characteristics, which exhibits huge potential in the application of memory and tunable optoelectronic devices. However, the fabrication of λ-Ti3 O5 still presents a great challenge and its application needs further investigation. In this work, we developed a novel method to fabricate nanocrystalline λ-Ti3 O5 by carbothermal reduction of nano-TiO2, and explored its terahertz transmission properties through a temperature induced phase transition. A second phase was introduced to inhibit the grain growth of titanium oxide during the carbothermal reduction, by performing a surface modification of the precursor nano-TiO2 particles with Al2 O3 . This process was proved to be critical for the formation of nanocrystalline λ-Ti3 O5 . An in situ XRD analysis combined with a first-principles calculation based on plane wave DFT indicated that the nanocrystalline λ-Ti3 O5 exhibited a semimetallic λ phase to metallic α phase transition across a large temperature range. The phase transition was accompanied by continuous, slow and reversible tuning of the terahertz transmission amplitude. This work provides considerable insights into the synthesis of λ-Ti3 O5 and opens up studies on the applications of λ-Ti3 O5 in the THz range, such as but not limited to sensors and smart windows.